2011
DOI: 10.1016/j.bandc.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Attentional disengagement in adults with Williams syndrome

Abstract: Williams syndrome (WS) is a neurodevelopmental disorder characterized by a distinctive behavioral and cognitive profile, including widespread problems with attention. However, the specific nature of their attentional difficulties, such as inappropriate attentional allocation and/or poor attentional disengagement abilities, has yet to be elucidated. Furthermore, it is unknown if there is an underlying difficulty with the temporal dynamics of attention in WS or if their attentional difficulties are task-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(80 reference statements)
0
4
0
1
Order By: Relevance
“…This atypical gaze has two explanations that are related to atypical explicit attentional control or visual attention processing captured by faces in individuals with WS. The first possibility is that prolonged fixation on a target-unrelated face is caused by atypical explicit attentional control of attentional shifting [ 23 ] or disengagement [ 24 , 25 ]. Posner et al [ 26 ] suggested that the cognitive act of shifting attention from one focus to another involves three distinct processes: disengagement of attention from the current focus, moving attention to a new target, and engagement of the new target.…”
Section: Discussionmentioning
confidence: 99%
“…This atypical gaze has two explanations that are related to atypical explicit attentional control or visual attention processing captured by faces in individuals with WS. The first possibility is that prolonged fixation on a target-unrelated face is caused by atypical explicit attentional control of attentional shifting [ 23 ] or disengagement [ 24 , 25 ]. Posner et al [ 26 ] suggested that the cognitive act of shifting attention from one focus to another involves three distinct processes: disengagement of attention from the current focus, moving attention to a new target, and engagement of the new target.…”
Section: Discussionmentioning
confidence: 99%
“…Many children and adults with Williams syndrome gravitate to either making music or listening to music, and their initial attractions to music may be associated with altered auditory processing and fascinations with sound [Lense and Dykens, , Lense and Dykens, in press]. Using neural imaging and psychoacoustic tests, Wengenroth et al [] found extreme holistic sound perception in Williams syndrome, seen in functional and structural leftward asymmetry of the auditory cortex.…”
Section: Why Hasn't Aging In Rare Intellectual Disability Syndromes Bmentioning
confidence: 99%
“…ADHD is seen in up to 65% of children with Williams syndrome [e.g., Leyfer et al, ], and diminished hyperactivity but persistent distractibility and inattention is noted in the vast majority of adults [Elison et al, 2010]. Persistent inattention is associated with problems with disengaging attention, as seen in an intense focus on faces, and in a prolonged attentional blink, or difficulty detecting a second visual target when it is presented in close temporal proximity to an initial target [Lense et al, ].…”
Section: Why Hasn't Aging In Rare Intellectual Disability Syndromes Bmentioning
confidence: 99%
“…En el plano del desarrollo cognitivo, el ritmo y las trayectorias de desarrollo son diferentes en el SD y SW. Mientras que los niños con SD presentan ciertas ventajas en la capacidad de atención conjunta, en los niños con SW, estas capacidades son muy débiles, lo que podría tener un efecto acumulativo, no solo en su desarrollo lingüístico sino también en la calidad de sus interacciones sociales (Laing et al, 2002). Para los niños con SD, la atención sostenida suele ser de corta duración y menos frecuente (Brown et al, 2003), mientras que, para los niños con SW, se trata de un punto fuerte relativo, aunque existen indicios de que tienen muchas dificultades para desengancharse del estímulo (Brown et al, 2003; Lense, Key, & Dykens, 2011). Las personas con ambos síndromes presentan un gran interés por la interacción cara a cara.…”
Section: Influencia Dinámica Entre La Interacción Padre/madre-hijo Y ...unclassified
“…While children with DS have some strengths in joint attention skills, in children with WS these skills are weak and may arguably have a knock-on effect not only on their early language development, but also on the quality of their social interactions (Laing et al, 2002). In DS, sustained attention tends to be short and less frequent (Brown et al, 2003), while in WS it is a relative strength, although there is an indication that they lack the ability to disengage from a stimulus (Brown et al, 2003; Lense, Key, & Dykens, 2011). Increased interest in face-to-face-interaction is evident in both syndromes.…”
mentioning
confidence: 99%